2012
DOI: 10.1093/qjmed/hcs045
|View full text |Cite
|
Sign up to set email alerts
|

Contact tracing in pulmonary and non-pulmonary tuberculosis

Abstract: Contact tracing in low-prevalence TB countries, for both pulmonary and non-pulmonary TB, is an essential intervention to identify and reduce the number of infected patients that will progress to active disease. This is the key for effective TB control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 13 publications
1
11
0
2
Order By: Relevance
“…One risk factor associated with the onset of LTBI is the location of 3,6 These results indicate that contacts present a higher frequency of TB than the general population, especially those with risk factors, such as children. 14,15 As expected, 3,12,16 These factors have previously been identified by other authors 9,11,18,19 as being associated with non-compliance. Non-compliance among foreigners may often be due to their working conditions, because they are often employed in precarious jobs where taking time off to attend the recommended appointments could result in loss of earnings or employment.…”
Section: Considering the Location Of Tb (supporting
confidence: 78%
“…One risk factor associated with the onset of LTBI is the location of 3,6 These results indicate that contacts present a higher frequency of TB than the general population, especially those with risk factors, such as children. 14,15 As expected, 3,12,16 These factors have previously been identified by other authors 9,11,18,19 as being associated with non-compliance. Non-compliance among foreigners may often be due to their working conditions, because they are often employed in precarious jobs where taking time off to attend the recommended appointments could result in loss of earnings or employment.…”
Section: Considering the Location Of Tb (supporting
confidence: 78%
“…In order to exclude past infection, we excluded all contacts with a previous history of TB or past exposure to TB disease. Other studies, namely from low TB incidence countries, have also shown a greater risk for positive screening among the oldest [9,10] strengthening the hypothesis of greater host susceptibility.…”
mentioning
confidence: 76%
“…8,9 The World Health Organization (WHO) recommends that all children aged ≤ 5 years living with a smear-positive adult TB patient be screened. 10 Screening this population of children is one strategy to eliminate TB. 11 About 10% of children with latent TB infection develop signs and symptoms of TB disease.…”
Section: Discussionmentioning
confidence: 99%